The Heritability of Trust and Trustworthiness Depends on the Measure of Trust - Nathan Kettlewell; Agnieszka Tymula (Institute of Labor Economics (IZA), 2021)
Using a large sample of 1,120 twins, we estimated the heritability of trust using four distinct measures of trust – domain-specific political trust, general self-reported trust, and incentivized behavioral trust and trustworthiness. Our results highlight the importance of measuring trust in a context because its heritability differs substantially across the four measures, from 0% to 37%. Moreover, we provide the first evidence on the heritability of political trust which we estimate to be 37%. Furthermore, like the heritability, the environmental correlates of trust also vary across the different measures with political trust having the largest set of environmental covariates. The perceptions of COVID-19 health and income risks are among the unique correlates of political trust, with participants who are more worried about financial and health consequences of COVID-19, trusting politicians less, stressing the importance of trust in political leaders during a health crisis.
Keywords: D91; Z13; 330; trust; heritability; genetics; twin study